2012
DOI: 10.1186/1472-698x-12-19
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns of childhood diarrhoea in rural Uganda: a cross-sectional survey

Abstract: BackgroundDiarrhoea is the second leading cause of death in children under five accounting for 1.8 million deaths yearly. Despite global efforts to reduce diarrhoea mortality through promotion of proper case management, there is still room for ample improvement. In order to seek options for such improvements this study explored the knowledge and practices of diarrhoea case management among health care providers at health centres and drug shops in Uganda.MethodsRecords were reviewed for case management and stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…It found that knowledge was strongly associated with level of education. 41 As with present study, age, sex, and having received any formal medical trainings, were also shown to have no significant relationship with knowledge in a previous study that was conducted in Kogi and Kwara states. 14 Regular recommendation of ORS was reported by 87% of participants in this study, whereas 64% of PPMVs reported regular recommendation of zinc.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…It found that knowledge was strongly associated with level of education. 41 As with present study, age, sex, and having received any formal medical trainings, were also shown to have no significant relationship with knowledge in a previous study that was conducted in Kogi and Kwara states. 14 Regular recommendation of ORS was reported by 87% of participants in this study, whereas 64% of PPMVs reported regular recommendation of zinc.…”
Section: Discussionsupporting
confidence: 50%
“…44 It has, however, been reported by one study that there was a significant gap between knowledge and documented practices, and though health workers reported carrying out an activity, this did not reflect what was actually done. 7,41 High knowledge score, ORS availability at time of survey and zinc supplement use were significant predictors of ORS recommendation. This study also reports that awareness and possession of treatment guidelines, stocking of zinc, recommendation of ORS, as well as satisfactory knowledge category were strong predictors of recommendation of zinc.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It accounts 1.8 million deaths annually. Majority of these death happen in South Asia and Africa [4]. In Ethiopia, diarrhea remains a serious public health problem as it is the major killer of children with an estimated 73,700 deaths of under-ve children.…”
Section: Introductionmentioning
confidence: 99%